Polymer Materials in Additive Manufacturing: Modelling and Simulation - Shirinbayan, Mohammadali; Zirak, Nader; Benfriha, Khaled; Farzaneh, Sedigheh; Fitoussi, Joseph (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Additive manufacturing (AM) has been at the center of attention of studies and industry. The AM process involves gradual build-up in layers, and capability in the fabrication of complex shapes with low cost. Advances in the processing of polymers and polymer composites with this method are in the domain of this journal, which can provide a vital resource for anyone involved in additive manufacturing. This Special Issue cover original reviews and research articles dedicated to: AM processes of manufacturing and materials; Process-microstructure/morphology-properties relationships; Optimization of process parameters; Mechanical properties of fabricated parts; Modeling and simulation.